On evil and computational creativity. Issue 2 (2nd April 2016) - Majid al-Rifaie, Mohammad; Cropley, Arthur; Cropley, David; Bishop, Mark
ABSTRACT: This paper touches upon the philosophical concept of evil in the context of creativity in general, and computational creativity in particular. In this work, dark creativity is introduced and linked to two important pre-requisites of creativity (i.e. freedom and constraints). A hybrid computational system is then presented; it includes one swarm intelligence algorithm, Stochastic Diffusion Search – mimicking the foraging behaviour of one species of ant, Leptothorax acervorum – and one physiological mechanism – imitating the behaviour of human immunodeficiency virus. The aim is to outline an integration strategy deploying the search capabilities of the swarm intelligence algorithm and the destructive power of the digital virus. The swarm intelligence algorithm determines the colour attribute of the dynamic areas of interest within the input image, and the digital virus modifies the state of the input image, creating the projection of "evil" over time (evil is used here as excessive use of underlying freedom). The paper concludes by exploring the significance of sensorimotor couplings and the impact of intentionality and genuine understanding of computational systems in the light of the philosophical concept of weak and strong computational creativity.